Implementation of Public Infrastructure, Facilities, and Utilities Development Assistance Program For Low-Income Community Housing in The City of Palembang According to Law Number 1 Year 2011 Concerning Housing and Settlement Area (Veteran Law Review, 2023)
The Public Housing Infrastructure, Facilities and Utilities Assistance Program for Low-Income Communities (MBR) is the government's support to realize livable housing for Low-Income Communities (MBR) as stipulated in Law Number 1 of 2011 concerning Housing and Settlement Areas. In South Sumatra Province, Palembang City with an area of slum areas based on the Governor's Decree in 2021 reaches 4,451 hectares and is one of the cities that is a priority to get handling of urban slum settlements from the Ministry of PUPR. In accordance with the existing problems, the objectives to be achieved in this study are to determine the implementation of the infrastructure development assistance program in the form of low-income community housing roads in the city of Palembang and to determine the factors that influence the implementation of the infrastructure development assistance program in the form of low-income community housing roads. in the city of Palembang. The method used in this study in discussing the existing problems, the author uses two approaches, namely: a normative juridical approach and an empirical juridical approach. The data used in this study were sourced from library research and field research. After the data is obtained and collected, then it is analyzed descriptively which produces descriptive data in the form of written or spoken words from sources that can be understood. Then in analyzing the data, the author uses a qualitative method, which is a method of analyzing the data collected and then described in words or sentences, separated according to categories so that the final conclusion is obtained. The results and discussion in this study show that the implementation of the PSU Assistance Program in the form of roads can be seen from the following: First, the PSU Assistance Budget, the financial realization in the 2021 fiscal year reached 75.47% of the total budget ceiling, while the physical realization reached 72, 36%. Second, the amount of PSU Assistance in Palembang City, the implementation of PSU Assistance for MBR housing roads is not optimal and is less significant between the annual performance target and the performance agreement of the South Sumatra Province Housing Provision Work Unit. Only 18.89% can be achieved from the annual performance target of 1800 units in 2021. Of that number in Palembang City, there are 124 units. Third, the performance of the South Sumatra Provincial Housing Provision Work Unit, Ministry of PUPR, during the 2021 fiscal year, the activities and programs carried out were less than optimal. However, the performance of the Housing Provision Work Unit in 2021, especially in the housing road PSU Assistance program for MBR, has improved performance, because in 2020 there has been no implementation of PSU construction while in 2021 it has successfully implemented 340 units in South Sumatra Province while 124 units for the City Palembang. Factors influencing the implementation of the PSU Assistance program in the form of roads in Palembang City consist of supporting factors, namely: budget, the application process can be carried out anywhere or online with a web-based application, the number of low-income housing in Palembang City. While the inhibiting factors are: the Covid-19 pandemic, lack of technical staff, weather, coordination between stakeholders, at least proposals for PSU assistance submitted by developers. Suggestions that can be given to the Housing Supply Satker of South Sumatra Province are to improve planning, implementation, supervision and control of housing development, so that the performance targets that have been set can be realized maximally, and the implementers of the Palembang City PSU Assistance Program are more active in providing socialization to members associations for a more even and in-depth understanding. For the Ministry of PUPR so that the requirements for applying for road PSU Assistance for MBR Housing are updated to make it easier for developers to meet the requirements and get road PSU Assistance for MBR Housing, especially in the city of Palembang. And for developers to be more active in seeking information about the requirements and programs at the Ministry of PUPR, so that they can obtain the latest information and regulations to realize the goals and the common good.